Understanding social policy - Hill, Michael J. (Michael James), 1937- (Oxford, UK ; Malden, Mass. : Blackwell, 1997)
What is social policy? The history of social policy. The making of social policy. Implementation. Social security. The health service. The personal social services. Education. Employment policy...
Keywords: Great Britain; Social policy; Welfare state; Welfare economics; Welfare state; Welfare economics; Great Britain -- Social policy; Great Britain -- Social policy